Notes, with Sketches of Mason Marks on the Cathedral of St Machar, Old Aberdeen (Proceedings of the Society of Antiquaries of Scotland, 1867)
A collection of mason’s marks were uncovered on the walls of St Machar’s Cathedral during repairs to the roof. Notes of the marks’ placements and speculation about when sections of the cathedral were constructed accompany the illustrations.